High-conductivity flexible Ag films formed by low-temperature and short-time sintering of PVP-modified silver oxalate composite ink. (27th January 2022) - Fan, PeiYuan; Zhang, WenHua; Yu, Xianglei; Gan, GuoYou
Abstract: Attaining low-temperature sintering and high electrical conductivity is vital in the field of flexible electronics. Inks with silver oxalate as the precursor have recently received significant attention in this field; however, the high sintering temperature and long sintering time limit commercial applicability. High sintering temperature can shorten the sintering time but lead to porous and uneven film morphology; thus, reducing the conductivity. On the other hand, low sintering temperature prolongs the sintering time; thus, reducing the production efficiency. To solve the abovementioned problems, a silver composite conductive ink modified by polyvinylpyrrolidone (PVP) was prepared in this study. The ink used silver oxalate as the precursor, methanol and acetone as the solvent, and 1, 2-diaminopropane as the complexing agent, and could reduce the sintering temperature and time to 160 °C and 20 min, respectively. After sintering, the silver film showed good electrical conductivity, and low resistivity (4.56 μ Ω·cm). Furthermore, the impact of sintering temperature on the surface morphology and electrical conductivity were also studied, and the results showed that PVP had a positive influence on the nucleation of silver and the microstructure of the sintered silver film.